Shigella IpaD has a dual role: signal transduction from the type III secretion system needle tip and intracellular secretion regulation - Roehrich, A Dorothea (Blackwell Publishing Inc, 2013)
Type III secretion systems (T3SSs) are protein injection devices essential for the interaction of many Gram-negative bacteria with eukaryotic cells. While Shigella assembles its T3SS when the environmental conditions are appropriate for invasion, secretion is only activated after physical contact with a host cell. First, the translocators are secreted to form a pore in the host cell membrane, followed by effectors which manipulate the host cell. Secretion activation is tightly controlled by conserved T3SS components: the needle tip proteins IpaD and IpaB, the needle itself and the intracellular gatekeeper protein MxiC. To further characterize the role of IpaD during activation, we combined random mutagenesis with a genetic screen to identify ipaD mutant strains unable to respond to host cell contact. Class II mutants have an overall defect in secretion induction. They map to IpaD's C-terminal helix and likely affect activation signal generation or transmission. The Class I mutant secretes translocators prematurely and is specifically defective in IpaD secretion upon activation. A phenotypically equivalent mutant was found in mxiC. We show that IpaD and MxiC act in the same intracellular pathway. In summary, we demonstrate that IpaD has a dual role and acts at two distinct locations during secretion activation.